Penerapan Prinsip Syariah pada Akad Rahn di Lembaga Pegadaian Syariah - Lamtana Lamtana; Vemmy Mayditri (STKIP PGRI SITUBONDO, 2022)
Non-Bank Islamic Financial Institutions in Indonesia, one of which is the Sharia Pawnshop, to implement various kinds of products and contracts in carrying out their business activities, one of the products is the Rahn contract, the freedom to design the form of the contract will provide product diversity, however fiqh analysis is carried out to avoid things that are prohibited, considering that one of the rules in ushul fiqh is basically all transactions are allowed unless there is a clear argument forbidding it. Based on the pillars of Rahn's contract in practice, starting from marhun, marhun bih, shighah, and 'aqidaini, it is in accordance with sharia theory. Pawn as one of the categories of debt-receivable agreements, for a trust from the creditor, the debtor pledges the goods as collateral for the debt. The collateral remains the property of the person who pawned it, but is controlled by the recipient of the pledge. The results of this study show that in general the Sharia Pawn Sharing the Blessing of Samarinda has complied with the rules in rahn transactions. Pawn Sharia Sharing Blessings in other words using multiple contracts (al-uqud al-murakkabah). It is a hybrid contract (multi-contract), namely rahn (pawning), qardh (borrowing) and ijarah (rental) contracts. The second contract responds to the first contract, and the third contract completes the second contract where the perfection of the first contract depends on the perfection of the second and third contracts through a reciprocal process or one contract depends on another contract. Tthe auction system carried out by sharia pawnshops is in accordance with the DSN-MUI Fatwa No: 25/DSN-MUI/III/2002 concerning Rahn. Excess money from the auction after deducting loans and fees will be returned to the customer, while if there is still a shortage, it remains the customer's obligation to pay off. This is the beauty of Islam where loan settlement or repayment is carried out fairly